Second-hand smoke exposure among undergraduates and support for smoke free campuses in Lagos, Nigeria - Yetunde Atiba; Oluwakemi Ololade Odukoya; Tope Olubodun (Tobacco Induced Diseases, 2018)
Background Smoke free policies are increasingly being enacted in many countries. Lagos state recently passed a state-wide smoke free law. However, campuses were excluded from the list of public places where smoking would be disallowed. This study aimed to assess the second-hand smoke (SHS) exposure among university undergraduates and assess their support for smoke free campuses.